Do Financial Concerns Make Workers Less Productive? - Kaur, Supreet; Mullainathan, Sendhil; Oh, Suanna; Schilbach, Frank (Quarterly Journal of Economics, 2025)
Abstract Workers who are worried about their personal finances may find it hard to focus at work. If so, reducing financial concerns could increase productivity. We test this hypothesis in a sample of low-income Indian piece-rate manufacturing workers. We stagger when wages are paid out: some workers are paid earlier and receive a cash infusion while others remain liquidity constrained. The cash infusion leads workers to reduce their financial concerns by immediately paying off debts and buying household essentials. Subsequently, they become more productive at work: their output increases by 7% (0.11 std. dev.), and they make fewer costly, unintentional mistakes. Workers with more cash on hand thus not only work faster but also more attentively, suggesting improved cognition. These effects are concentrated among more financially constrained workers. We argue that mechanisms such as gift exchange or nutrition cannot account for our results. Instead, our findings suggest that financial strain, at least partly through psychological channels, has the potential to reduce earnings exactly when money is most needed.